LEXICAL-STYLISTICS IN THE NOVEL "NIGHT AND DAY" USE OF MEANS OF EXPRESSION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
"Theory of Translation" is designed to provide students with the necessary theoretical knowledge to understand the complex phenomenon of translation. The lectures cover topics such as the history of translation, the evolution of translation studies, and key concepts in linguistics relevant to translation theory. These include bilingualism, the translation process, translation models, and specialized translations of scientific literature.